Estrategia de re-branding turístico basado en el diseño de experiencias, para elevar el posicionamiento del Cantón Baños - Mantilla Barrera, Kevin Enrique (2021)
This research aims to propose a strategy for rebranding tourism through the design of experiences in the year 2021. The application of the Anholt index methodology, the Robert Scott methodology, and the Drag- and-Drop methodology is necessary to determine the appropriate strategy for a correct operation and positioning. With this research topic, it is planned to define the territorial brand of Baños de Agua Santa, which allows establishing an emotional link with the inhabitants and tourists. Once the tools were applied to analyze and validate the results, a series of brand proposals were established, subject to studies. This will allow us to determine graphic and compositional elements that will give life to the brand of the canton Baños de Agua Santa. Through the background of communication that was used in the previous graphic identity, we were able to determine as a tourism rebranding strategy based on the design of experiences, the design of personalized souvenirs that will give life to the brand concept, linked to a Web page landing page of content through a QR code. With this research work, it was possible to obtain a tourist brand that connects with a cosmopolitan community of visitors. Likewise, the souvenirs and the landing web page create that emotional link between the brand and the user.